EFFORTS TO INCREASE EXCLUSIVE BREASTFEEDING AMONG POSTPARTUM MOTHERS - Okta Zenita Siti Fatimah; Seventina Nurul Hidayah (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Exclusive breastfeeding is crucial for improving maternal and infant health and reducing neonatal morbidity and mortality, yet implementation obstacles remain. Preliminary observations at Pasar Rebo Regional General Hospital (RSUD), East Jakarta, showed suboptimal exclusive breastfeeding coverage, with only 65% of mothers breastfeeding exclusively during care, while others used formula or faced difficulties. This qualitative case study aimed to evaluate efforts to increase exclusive breastfeeding at RSUD Pasar Rebo. Using purposive sampling, 15 informants were selected: 5 experienced healthcare workers (midwives, nurses, lactation counselors) and 10 postpartum mothers (days 1–42). Data were gathered through in-depth interviews, Focus Group Discussions, and direct observations, then analyzed using content and thematic analysis. Results identified key efforts: breastfeeding education, Early Initiation of Breastfeeding (EIBF/IMD), rooming-in, and technique counseling. Supporting factors included available healthcare staff, hospital policies, and family support. Conversely, main barriers were maternal lack of knowledge, postpartum fatigue, and misconceptions about milk supply. Although efforts exist, continuous education and support remain essential.